The impact of sexual counseling training on nurses’ responsibility and practice of sexual counseling for patients with myocardial infarction - Somayeh Kalantaripoor; Mahlagha Dehghan; Mohammad Ali Zakeri; Parvin Mangolian shahrbabaki (BMC Nursing)
Abstract Background Patients who have had myocardial infarction often feel afraid and anxious about having sex again. This study examined the impact of sexual counseling training on nurses’ responsibility and practice of sexual counseling for patients with myocardial infarction. Methods This study utilized a quasi-experimental design involving 76 nurses working in cardiac care units (CCUs) of hospitals in southeastern Iran in 2023. Participants were randomly assigned to intervention and control groups. The intervention group participated in sexual counseling educational workshops, which consisted of two 1.5-hour sessions held one month apart. The Sex After MI Knowledge Test was used to evaluate the nurses’ responsibility and practice of sexual counseling for patients with myocardial infarction before and after the intervention. Results The findings revealed that the mean responsibility score in the intervention group increased from 9.06 ± 2.50 to 12.15 ± 1.37 after the intervention. The practice score of nurses in the intervention group increased from 7.21 ± 5.58 to 14.91 ± 4.58. There was a significant difference in responsibility and practice scores between the intervention and control groups after the intervention (P < 0.001). Conclusion The study demonstrated that training improved nurses’ responsibility and practice. Before the training, their scores were low, but they significantly increased afterwards. Sexual counselling improved nurses’ practice and responsibility when caring for patients with myocardial infarction so it is recommended for nurses in CCU. Clinical trial number Not applicable.